When a Pesticide Doesn't Work - Frederick M. Fishel (EDIS, 2008)
PI-163, a 4-page illustrated fact sheet by Frederick M. Fishel, describes several factors contributing to pesticide failure. Includes references. Published by the UF Department of Agronomy, May 2008.